2019
DOI: 10.1080/16549716.2019.1587893
|View full text |Cite
|
Sign up to set email alerts
|

A learning health systems approach to improving the quality of care for patients in South Asia

Abstract: Poor quality of care is a leading cause of excess morbidity and mortality in low-and middleincome countries (LMICs). Improving the quality of healthcare is complex, and requires an interdisciplinary team equipped with the skills to design, implement and analyse settingrelevant improvement interventions. Such capacity is limited in many LMICs. However, training for healthcare workers in quality improvement (QI) methodology without buy-in from multidisciplinary stakeholders and without identifying setting-specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 21 publications
(28 reference statements)
0
14
0
Order By: Relevance
“…Poor quality of care is one of the leading causes of mortality in LMIC, and contributed to five million deaths based on data from the 2016 Global Burden of Disease study [ 118 ]. However, additional challenges are noted for LMIC, including limited resources to electronically collect data at the point of care and evaluate the impact of quality improvement initiatives on patient outcomes [ 119 ]. There is also little standardization of patient health records and hospital forms, which makes the use of routine clinical data a challenge [ 90 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Poor quality of care is one of the leading causes of mortality in LMIC, and contributed to five million deaths based on data from the 2016 Global Burden of Disease study [ 118 ]. However, additional challenges are noted for LMIC, including limited resources to electronically collect data at the point of care and evaluate the impact of quality improvement initiatives on patient outcomes [ 119 ]. There is also little standardization of patient health records and hospital forms, which makes the use of routine clinical data a challenge [ 90 ].…”
Section: Resultsmentioning
confidence: 99%
“…Quality improvement initiatives in LMIC tend to be externally led, with limited insight into contextual barriers and/or lacking local evidence. It is important that learning systems include representation from interprofessional teams working at the point of care and that initiatives are adapted to the local context [ 105 , 119 ].…”
Section: Resultsmentioning
confidence: 99%
“…Overcoming the barriers and bottlenecks to efficient organisational delivery of AMI care (both structure and process) is fundamental to improving the quality of care. 29Work already published by the authors as part of a health systems improvement network have highlighted additional bottlenecks in organisational structure, process and patient-centred- in care. 29 Focus groups held with frontline healthcare workers to map the pathways of AMI care revealed that diagnosis of AMI was delayed due to inconsistencies in patients’ timeliness of presentation, accessibility of ECG investigation for patients when presenting with the symptoms of syndromic acute coronary syndrome and delays in reporting of ECG.…”
Section: Discussionmentioning
confidence: 99%
“…To date, in LMICs, QI initiatives have had limited success in achieving sustained change or have proven difficult to scale [5]. Quality improvement methods are generally neither an established part of medical education nor are they a priority investment for healthcare institutions in resource-limited settings [5,9].…”
Section: Limited Success Of Quality Improvementmentioning
confidence: 99%